Social Status Differentially Affects Behavioral and Immunological Outcomes of Group-Kept Sows Fed Different Dietary Fiber Using Different Length Feeding Barriers - Pacheco, Eridia; Lopez, Mayra; Salak-Johnson, Janeen L. (Frontiers in Animal Science, 2021)
Social conflict is inevitable among group-housed sows and may contribute to poorer welfare among those sows experiencing more social stress. The degree of individual welfare is associated with social position within the group. Therefore, this study examined the effects of social status on behavior, immune, endocrine, and productivity of group-housed pregnant sows fed a diet supplemented with 30% wheat middlings and 15% soybean hulls (MID-SH) or 30% distillers dried grains with solubles and 30% corn germ meal (DDGS-GM) and in pens with individual feeding places made from short (58.4 cm) or long (203.2 cm) barriers. A 2 × 2 factorial design resulted in 4 experimental treatment groups (n = 9 sows/diet-length-block combination): (1) MID-SHshort; (2) MID-SHlong; (3) DDGS-GMshort; (4) DDGS-GMlong. Groups of sows equally representing all diet-length combinations across 4 blocks (n = 36 sows/block) were subjected to a feeding competition test to identify highest (dominant) and lowest (subordinate) ranked sows within each group resulting in 64 sows (n = 16 sows/treatment; n = 32 sows/social status). Data revealed 2- and 3-way interactive effects on aggressive behavior (P < 0.005), postural (P < 0.01), oral (P < 0.0001), and eating (P < 0.005) behaviors, sow mean body weights and gains (P < 0.05) and litter weaning weights (P < 0.05), especially among subordinates in pens with long barriers. Subordinates in pens with long barriers received 21% less aggression and were 73% less likely to be displaced than subordinates in pens with short ones (P < 0.0001). Dietary treatment also influenced some of these measures among the subordinates in pens with long barriers. For example, subordinates in DDGS-GMlong received 64 and 67% less aggression than subordinates in DDGS-GMshort and MID-SHshort (P < 0.005). Eat bouts were greatest among subordinates in MID-SHlong, and sitting and sham-chewing were less. However, those in DDGS-GMlong spent less time standing and laying, and their litters were 15.28 kg heavier (P = 0.01), but overall subordinates fed DDGS-GM diet were lightest and gained less total body weight than those fed MID-SH (P < 0.05). Other measures such as neutrophil-to-lymphocyte ratio were elevated among dominants in MID-SHlong (P < 0.05); whereas, cortisol (P = 0.06) was lowest and glucose (P = 0.09) highest for subordinates in DDGS-GMlong. These data imply that subordinates benefited from being housed in pens with long barriers, but the type of dietary fiber consumed differentially influenced behavioral budget and several sow- or litter-related traits among subordinates in pens with long barriers. In contrast, the subordinates in pens with short barriers had poorer welfare regardless of diet. Collectively, these data imply that social status is a crucial factor contributing to variation in individual well-being among group-housed sows and that sows of different social positions within a group may evoke different biological responses in an attempt to cope.